2011
DOI: 10.1016/j.physletb.2010.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Restricting UHECRs and cosmogenic neutrinos with Fermi-LAT

Abstract: Ultrahigh energy cosmic ray (UHECR) protons interacting with the cosmic microwave background (CMB) produce UHE electrons and gamma-rays that in turn initiate electromagnetic cascades on CMB and infrared photons. As a result, a background of diffuse isotropic gamma radiation is accumulated in the energy range $E\lsim 100$ GeV. The Fermi-LAT collaboration has recently reported a measurement of the extragalactic diffuse background finding it less intense and softer than previously measured by EGRET. We show that … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
183
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(198 citation statements)
references
References 33 publications
12
183
1
2
Order By: Relevance
“…Constraints seem to be more stringent using the photon background by Kneiske et al (2004), favored by the Fermi observations (Abdo et al 2010) and in this case the photon flux in the SFR evolution case appears to be very close to the Fermi bounds. Here, we confirm previous results by Berezinsky et al (2010a) and Ahlers et al (2010), claiming that in the framework of the dip model, the Fermi measurements of the diffuse gamma-ray flux actually involve strong limitations on the expected cosmogenic neutrino fluxes. By themselves, indeed, ruling out basically all models that yields neutrino fluxes higher than the SFR model, they imply neutrino fluxes almost an order of magnitude lower than the upper limit of the Pierre Auger Observatory (see Abraham et al 2009a,b;Tiffenberg et al 2009;Abreu et al 2001;and Fig.…”
Section: Dip Modelsupporting
confidence: 91%
See 2 more Smart Citations
“…Constraints seem to be more stringent using the photon background by Kneiske et al (2004), favored by the Fermi observations (Abdo et al 2010) and in this case the photon flux in the SFR evolution case appears to be very close to the Fermi bounds. Here, we confirm previous results by Berezinsky et al (2010a) and Ahlers et al (2010), claiming that in the framework of the dip model, the Fermi measurements of the diffuse gamma-ray flux actually involve strong limitations on the expected cosmogenic neutrino fluxes. By themselves, indeed, ruling out basically all models that yields neutrino fluxes higher than the SFR model, they imply neutrino fluxes almost an order of magnitude lower than the upper limit of the Pierre Auger Observatory (see Abraham et al 2009a,b;Tiffenberg et al 2009;Abreu et al 2001;and Fig.…”
Section: Dip Modelsupporting
confidence: 91%
“…More recently, the Fermi satellite measurements (Abdo et al 2010) reported a gamma-ray background between 100 MeV and 100 GeV lower than previously estimated using EGRET data. The additional constraints allowed by this new measurement were discussed by Berezinsky et al (2010a), Ahlers et al (2010) and more recently by Wang et al (2011). These studies agree that the constraints implied by this new estimate of the gamma-ray background are much more stringent than those using EGRET data, but their conclusions differ on the impact of these new constraints on the observability of UHE neutrino fluxes (see below).…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…More recently, the Fermi satellite measurements [182] reported a gamma-ray background between 100 MeV and 100 GeV lower than previously estimated using EGRET data. The additional constraints brought by this new measurement were discussed in [186,187] and more recently in [188,165]. The Fermi estimate of the diffuse gamma-ray background brings constraints on the most optimistic scenarios in terms of UHE neutrino fluxes involving UHECR produced by strongly evolving source (for instance the FR-II we mentioned earlier).…”
Section: Secondary Cosmogenic Messengersmentioning
confidence: 89%
“…A recent analysis of the diffuse extragalactic γ-ray background (EGRB) by Fermi-LAT [47] shows a γ-ray spectrum that is lower and softer than previous results of EGRET [48]. It has been argued that the Fermi-LAT flux constraints all-proton models of UHE CRs extending down to energies of the "second knee" [49], though the systematics of UHE CR measurements is not sufficient to entirely exclude this model at a statistically significant level [32].…”
Section: Electromagnetic Cascades From Heavy Nucleimentioning
confidence: 99%